Cassava in the Caribbean region : a look at the potential of the crop to promote agricultural development and economic growth - Organización de las Naciones Unidas para la Alimentación y la Agricultura (FAO) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
This document is an attempt to present an overview of the technological options that are currently available to promote increased productivity and competitiveness of the cassava crop. These options could become an excellent strategy for the difficult task faced by the countries in the region that need to reduce poverty, hunger and the increased dependency on imported foods to attend the nutritional needs of their populations.